Digital Skills For Eco-Innovative Entrepreneurship - Hamburg, Ileana; Bucksch, Sascha (Advances in Social Sciences Research Journal, 2017)
Eco-innovation refers to the development of products and processes that contribute to sustainable development and significantly decrease environmental impacts. This includes technological, social and institutional innovation. Entrepreneurship is a key driver of economy and social prosperity. Concepts as eco-innovative entrepreneurship emergedin connection with environmental problems.Entrepreneurship education programmes should offer students the tools to be creative, to solve also ecological problems efficiently, to analyze a business idea objectively, and to communicate, cooperate, lead, develop and evaluate projects. Referring digital skills, eco-innovative entrepreneurs should be able i.e. to iinteract and communicate through digital technologies, to share data and digital content through technology, to solve technical and environmental problems by using ICT, to use social media und e-mail for their marketing strategy, to be familiar with free digital tools and use them for marketing.The paper presents some issues of eco-innovation, literature in the field of entrepreneurship education and competences which are necessary to be an eco-innovative entrepreneur. Examples of projects worked by authors to achieve some competences are given.